Logarithms of a binomial series: a Stirling number approach - Prodinger, Helmut (Ars mathematica contemporanea, 2019)
The ?$p$?-th power of the logarithm of the Catalan generating function is computed using the Stirling cycle numbers. Instead of Stirling numbers, one may write this generating function in terms of higher order harmonic numbers.
Keywords: Catalan numbers; Catalanova števila; generating function; logaritem; logarithm; rodovna funkcija; Stirling number; Stirlingovo število